Cloning and Characterization of Glyceraldehyde-3-Phosphate Dehydrogenase from Orchid (Cymbidium goeringii) - Tian, Yun-Fang; Li, Han; Yuan, Xiu-Yun; Yang, Yu-Zhen; Cui, Bo (Asian Journal of Chemistry, 2014)
Total RNA of Cymbidium goeringii (C. goeringii) leaves was extracted with trizol. With primers designed based on the sequence of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) from NCBI, a full-length cDNA of GAPDH was cloned from C. goeringii by RT-PCR combined with RACE. The newly cloned GAPDH gene was designated as CgGAPDH1 (JQ978220). Sequence analysis shows that CgGAPDH1 is 1 424 bp in length, contains a single open reading frame from 168-1190 bp, encodes proteins with 340 amino acids. CgGAPDH1 showed 99 % similarity with GAPDH5 (JN177726). Phylogenetic analysis based on the sequence of GAPDH showed that C. goeringii had closely relation with Triticum aestivum and Lilium longiflor. Bioinformatics analysis indicated that CgGAPDH1 protein is soluble without transmembrane domain. Homology modeling of the GAPDH in C. goeringii based on the 3D structure is similar to that of homologues in Triticum aestivum, Oryza sativa and Zea mays, which firmed that the polypeptides were highly conserved.